A sea urchin-shaped SiO2 / PDVB / PDA / Apt composite microsphere, its preparation method and application

CN122894971APending Publication Date: 2026-10-13SHANDONG ACADEMY OF AGRICULTURAL SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611206362.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-10
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

然而,现有适配体功能化分离材料仍面临核心瓶颈:传统载体表面可修饰的官能团数量有限,导致适配体在材料表面的负载密度低,宏观上表现为材料对低密度脂蛋白的吸附容量不足,无法满足大规模临床样本分离的需求

Benefits of technology

(1)本发明制备的海胆状SiO2/PDVB/PDA/Apt复合微球具有独特的分级结构,通过三氟化硼乙醚催化二乙烯基苯阳离子聚合,在二氧化硅微球表面原位生长出高交联聚二乙烯基苯纳米纤维网络,形成类似海胆的形貌,为低密度脂蛋白的富集提供了大量微观结合位点和空间可及性,同时有利于吸附过程中的快速传质,显著提高了材料对低密度脂蛋白的吸附容量,最大吸附容量可达2700 μg/mg以上,远高于现有同类分离材料。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122894971A_ABST
    Figure CN122894971A_ABST
Patent Text Reader

Abstract

The application discloses urchin-like SiO2 / PDVB / PDA / Apt composite microspheres and a preparation method and application thereof, and belongs to the technical field of biological separation materials. The SiO2 / PDVB composite microspheres are prepared by dispersing silica microspheres in an organic solvent containing a surfactant, adding a catalyst and divinylbenzene to perform a cationic polymerization reaction; the SiO2 / PDVB / PDA composite microspheres are prepared by dispersing the SiO2 / PDVB composite microspheres in a buffer solution containing dopamine, performing an oxidative self-polymerization reaction under weak alkaline conditions, and coating a polydopamine coating layer on the surface of the SiO2 / PDVB composite microspheres; and the SiO2 / PDVB / PDA / Apt composite microspheres are prepared by dispersing the SiO2 / PDVB / PDA composite microspheres in a buffer solution containing an amino-modified low-density lipoprotein aptamer and performing an immobilization reaction. The urchin-like SiO2 / PDVB / PDA / Apt composite microspheres have a unique hierarchical structure, and the adsorption efficiency of the low-density lipoprotein can reach more than 90%, and the urchin-like SiO2 / PDVB / PDA / Apt composite microspheres exhibit extremely high selectivity. Competitive elution can be realized by using an aptamer complementary DNA chain as an eluent, and the elution efficiency can reach more than 85%, and progress is achieved in the separation or purification of low-density lipoprotein.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of bio-separation materials technology, specifically relating to a sea urchin-shaped SiO2 / PDVB / PDA / Apt composite microsphere, its preparation method, and its application. Background Technology

[0002] Low-density lipoprotein (LDL) is the main lipoprotein in plasma responsible for transporting endogenous cholesterol. Its structure consists of a core of hydrophobic cholesterol esters and triglycerides, and an outer layer composed of apolipoprotein B-100, free cholesterol, and phospholipids. Numerous epidemiological studies and clinical guidelines clearly indicate that long-term elevated plasma LDL cholesterol levels are an independent and important risk factor for cardiovascular and cerebrovascular diseases such as atherosclerosis, coronary heart disease, and stroke. Therefore, achieving efficient separation of LDL from complex biological samples such as blood and serum is not only crucial for the early clinical diagnosis and disease progression monitoring of hyperlipidemia, but also provides an indispensable pretreatment basis for exploring the molecular mechanisms of lipid metabolism disorders and screening novel biomarkers for cardiovascular diseases.

[0003] Currently, the separation of low-density lipoprotein (LDL) mainly relies on density gradient ultracentrifugation and immunoaffinity chromatography. However, ultracentrifugation is time-consuming and requires expensive equipment; while immunoaffinity chromatography offers high specificity, antibodies are costly, easily inactivated, and require stringent operating conditions. Traditional microsphere materials based on physical or electrostatic adsorption are less expensive, but they are easily contaminated by large amounts of plasma interfering proteins in complex biological matrices due to a lack of specificity. Furthermore, elution processes involving high salt, strong acid, or strong alkali can easily damage the native lipoprotein structure of LDL, severely affecting subsequent biological analyses.

[0004] In recent years, nucleic acid aptamers have gradually become an ideal alternative to antibody molecules due to their unique advantages. Aptamers can form highly specific spatial conformations with target molecules, and have significant advantages such as low cost, good chemical stability, ease of in vitro large-scale synthesis, and no immunogenicity, showing great potential in the fields of biosensing, clinical diagnosis, and targeted therapy. Currently, some studies have achieved preliminary targeted capture of low-density lipoprotein (LDL) by immobilizing LDL aptamers on material surfaces through physical adsorption or chemical cross-linking. However, existing aptamer-functionalized separation materials still face a core bottleneck: the limited number of functional groups that can be modified on the surface of traditional carriers leads to low aptamer loading density on the material surface, which macroscopically manifests as insufficient adsorption capacity of the material for LDL, failing to meet the needs of large-scale clinical sample separation.

[0005] Therefore, designing an aptamer separation platform that combines high adsorption capacity and high selectivity is a technical challenge that urgently needs to be solved in this field. Summary of the Invention

[0006] To address the problems existing in the prior art, this invention provides a sea urchin-shaped SiO2 / PDVB / PDA / Apt composite microsphere, its preparation method, and its application. This composite microsphere has the combined properties of high adsorption capacity, high selectivity, and mild elution, providing a novel material platform for the separation and purification of low-density lipoproteins and lipidomics research.

[0007] This invention is achieved through the following technical solution: In a first aspect, the present invention provides a method for preparing urchin-shaped SiO2 / PDVB / PDA / Apt composite microspheres, comprising the following steps: (1) Preparation of SiO2 / PDVB composite microspheres: Silica microspheres were dispersed in an organic solvent containing surfactants, and a catalyst and divinylbenzene were added to carry out cationic polymerization (a polyvinylbenzene nanofiber network was grown in situ on the surface of silica microspheres through cationic polymerization) to obtain SiO2 / PDVB composite microspheres. (2) Preparation of SiO2 / PDVB / PDA composite microspheres: The SiO2 / PDVB composite microspheres prepared in step (1) are dispersed in a dopamine solution and subjected to an oxidative self-polymerization reaction under weakly alkaline conditions. A polydopamine coating is then applied to the surface of the SiO2 / PDVB composite microspheres to obtain SiO2 / PDVB / PDA composite microspheres. (3) Preparation of SiO2 / PDVB / PDA / Apt composite microspheres: The SiO2 / PDVB / PDA composite microspheres prepared in step (2) are dispersed in a buffer solution containing amino-modified low-density lipoprotein aptamers and immobilized (the aptamers are immobilized on the surface of the polydopamine coating through non-covalent interactions) to obtain SiO2 / PDVB / PDA / Apt composite microspheres.

[0008] Furthermore, the nucleic acid sequence of the amino-modified low-density lipoprotein aptamer described in step (3) is shown in SEQ ID NO.1, with an amino group modified at its 5' end.

[0009] Further, in step (1), the particle size of the silica microspheres is 1~3μm; the catalyst is boron trifluoride diethyl ether; the surfactant is Span 80; and the organic solvent is n-heptane.

[0010] Further, in step (1), the mass ratio of silica microspheres to divinylbenzene is 1:3~8; the catalyst is boron trifluoride diethyl ether; the volume ratio of the catalyst to divinylbenzene is 1:5~15; the amount of surfactant added is 1 / 3~2 / 3 of the mass of silica; and the concentration of silica in the organic solvent is 3~6 mg / mL.

[0011] Further, in step (1), the cationic polymerization reaction is carried out under ultrasonic treatment at room temperature for 10-30 minutes, and anhydrous ethanol is added to terminate the reaction after the reaction is completed.

[0012] Further, in step (2), the concentration of dopamine in the buffer solution is 0.3~1.0 mg / mL; further, the buffer solution is a Tris-HCl buffer solution with pH 8.0~9.0.

[0013] Further, in step (2), the conditions for the oxidative self-polymerization reaction are: reacting for 20 to 60 minutes under weakly alkaline conditions of Tris-HCl buffer at pH 8.0 to 9.0.

[0014] Further, in step (3), the concentration of the amino-modified low-density lipoprotein aptamer in the buffer solution is 0.5~5 μmol / L; the buffer solution is a phosphate buffer or Tris-HCl buffer with pH 7.5~9.0.

[0015] Furthermore, in step (3), the conditions for the immobilization reaction are: room temperature, protection from light, and shaking reaction for 6~24h.

[0016] In a second aspect, the present invention provides sea urchin-shaped SiO2 / PDVB / PDA / Apt composite microspheres prepared by the above-described preparation method.

[0017] In a third aspect, the present invention provides the application of the aforementioned urchin-shaped SiO2 / PDVB / PDA / Apt composite microspheres in the separation of low-density lipoproteins.

[0018] Furthermore, the sea urchin-shaped SiO2 / PDVB / PDA / Apt composite microspheres are used to selectively adsorb and separate low-density lipoproteins from complex biological samples, including serum, plasma, or blood.

[0019] Furthermore, the adsorption conditions are: pH 4.5~6.5, temperature 20~37℃, and adsorption time 10~60min.

[0020] Furthermore, after the sea urchin-shaped SiO2 / PDVB / PDA / Apt composite microspheres adsorbed low-density lipoprotein, they were competitively eluted and recovered using aptamer complementary DNA strands, with an elution time of 20-60 min.

[0021] Furthermore, the urchin-shaped SiO2 / PDVB / PDA / Apt composite microspheres are used for the specific removal of low-density lipoprotein in the serum of patients with hyperlipidemia or for the separation and purification of low-density lipoprotein.

[0022] Furthermore, the purification process involves using the complementary DNA strand of the low-density lipoprotein aptamer as the eluent, with the elution conditions being the same as the adsorption conditions, to obtain high-purity low-density lipoprotein.

[0023] Compared with the prior art, the beneficial effects achieved by the present invention are as follows: (1) The sea urchin-shaped SiO2 / PDVB / PDA / Apt composite microspheres prepared in this invention have a unique hierarchical structure. Through the cationic polymerization of divinylbenzene catalyzed by boron trifluoride diethyl ether, a highly cross-linked polyvinylbenzene nanofiber network is grown in situ on the surface of silica microspheres, forming a sea urchin-like morphology. This provides a large number of microscopic binding sites and spatial accessibility for the enrichment of low-density lipoprotein. At the same time, it is conducive to rapid mass transfer during the adsorption process, which significantly improves the adsorption capacity of the material for low-density lipoprotein. The maximum adsorption capacity can reach more than 2700 μg / mg, which is much higher than that of existing similar separation materials.

[0024] (2) This invention improves the water dispersibility of SiO2 / PDVB composite microspheres by modifying the polydopamine interlayer. Simultaneously, as a stable bio-anchor, it achieves robust fixation of the amino-modified low-density lipoprotein aptamer, endowing the material with excellent selectivity for low-density lipoprotein. Under adsorption conditions of pH 5.5, the adsorption efficiency of the composite microspheres for low-density lipoprotein can reach over 90%, while the adsorption efficiency for interfering proteins such as human serum albumin, α-lactalbumin, β-lactoglobulin, and high-density lipoprotein is less than 40%, demonstrating extremely high selectivity.

[0025] (3) The present invention uses aptamer complementary DNA strand as eluent for competitive elution. Through base pairing competition, the specific binding between aptamer and low-density lipoprotein is effectively destroyed. The elution efficiency can reach more than 85% within 40 minutes. The elution conditions are mild and do not damage the natural lipoprotein core structure of low-density lipoprotein. The cholesterol recovery rate is more than 82%, effectively maintaining the structural integrity and biological activity of low-density lipoprotein.

[0026] (4) The composite microspheres of this invention successfully achieved the specific separation and recovery of low-density lipoprotein in goat serum simulating hyperlipidemia. SDS-PAGE verification results showed that after adsorption treatment with composite microspheres, the characteristic protein band of low-density lipoprotein in the serum was effectively removed, and only a single low-density lipoprotein band appeared in the elution recovery solution, indicating extremely high purity. This material has comprehensive properties of "specific recognition, efficient capture, gentle elution, and structural preservation," providing a promising material platform for the early screening, separation, purification, and biochemical metabolism research of low-density lipoprotein-related cardiovascular diseases.

[0027] (5) The method for preparing sea urchin-shaped SiO2 / PDVB / PDA / Apt composite microspheres of the present invention is simple, controllable, and low in cost, and is easy to scale up for production, and has good prospects for industrial application. Attached Figure Description

[0028] Figure 1 The images show scanning electron microscope (SEM) and transmission electron microscope (TEM) images of SiO2 / P, SiO2 / PP, and SiO2 / PP / Apt, where A is the SEM image of SiO2 / P, B is the SEM image of SiO2 / PP, C is the SEM image of SiO2 / PP / Apt, D is the TEM image of SiO2 / P, E is the TEM image of SiO2 / PP, and F is the TEM image of SiO2 / PP / Apt. Figure 2 Infrared spectra of SiO2 / P, SiO2 / PP, and SiO2 / PP / Apt; Figure 3 Thermogravimetric analysis curves for SiO2, SiO2 / P, SiO2 / PP, and SiO2 / PP / Apt; Figure 4 XPS spectra of SiO2, SiO2 / P, SiO2 / PP, and SiO2 / PP / Apt are shown, where A is the full XPS spectrum, B is the C1s spectrum, C is the N1s spectrum, and D is the O1s spectrum. Figure 5 The graph shows the effect of SiO2 / PDVB / PDA / Apt composite microsphere dosage and adsorption time on adsorption efficiency (low-density lipoprotein). A represents the dosage of SiO2 / PDVB / PDA / Apt composite microspheres, and B represents the adsorption time of the SiO2 / PDVB / PDA / Apt composite. Figure 6 The graph shows the effect of pH and ionic strength on the adsorption efficiency of low-density lipoprotein on SiO2 / PP / Apt. A represents pH and B represents ionic strength.

[0029] Figure 7 The adsorption efficiency of SiO2 / PP / Apt for different proteins is shown in the graph. Figure 8 The adsorption capacity of SiO2 / PP / Apt for different proteins is shown in the figure. Figure 9 The graphs show the adsorption performance of SiO2 / PP and SiO2 / PP / Apt for different proteins. A is the adsorption capacity graph for low-density lipoprotein at different concentrations, and B is the adsorption isotherm graph. Figure 10 The elution efficiency of low-density lipoprotein at different elution times is shown in the graph. Figure 11Electrophoresis images of protein components at different separation stages of goat serum with hyperlipidemia using SiO2 / PP / Apt: 1 is the protein molecular weight standard; 2 is the goat serum sample with added exogenous low-density lipoprotein standard; 3 is the supernatant after SiO2 / PP / Apt adsorption treatment; 4 is the protein solution recovered after competitive elution with aptamer complementary strands; 5 is the low-density lipoprotein standard. Detailed Implementation

[0030] The present invention is further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Experimental methods not specifically described in the following examples are generally performed under conventional conditions or as recommended by the manufacturer.

[0031] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of skill in the art. All reagents and materials used in this invention are readily available through conventional means, and unless otherwise specified, they shall be used in accordance with conventional methods in the art or as per the product instructions.

[0032] Example 1 (1) Preparation of SiO2 / PDVB composite microspheres: 10 mg of dehydrated sorbitan monooleate (Span 80) was mixed with 5 mL of n-heptane and dissolved by sonication. 20 mg of silica microspheres with a particle size of 2 μm were added and the mixture was stirred by sonication (600 W) for 15 min. 10 μL of boron trifluoride diethyl ether (BFEE) was added and stirred by sonication for 30 s. 100 μL of divinylbenzene (DVB) was added dropwise and the mixture was stirred by sonication (600 W) for 15 min to obtain an orange flocculent precipitate. Then, 100 μL of anhydrous ethanol was added to terminate the reaction and a white solid precipitate was obtained. The precipitate was washed with anhydrous ethanol and dried to obtain SiO2 / PDVB composite microspheres (SiO2 / P).

[0033] (2) Preparation of SiO2 / PDVB / PDA composite microspheres: 1 mg of dopamine hydrochloride was added to 2 mL of pH 8.5 Tris-HCl buffer (10 mM); then 1 mg of SiO2 / P composite microspheres prepared in step (1) were dispersed in the above dopamine hydrochloride buffer solution, stirred thoroughly for 30 min, centrifuged and washed with ultrapure water to obtain SiO2 / PDVB / PDA composite microspheres (SiO2 / PP).

[0034] (3) Preparation of SiO2 / PDVB / PDA / Apt composite microspheres: The SiO2 / PP composite microspheres prepared in step (2) were immersed in Tris-HCl buffer (10 mM) at pH 8.5 to oxidize the phenolic hydroxyl groups on the surface of the polydopamine coating into highly reactive quinone structures for surface activation; subsequently, the amino-modified low-density lipoprotein aptamer (SEQ ID NO.1: 5'-ACCTCGATTTTATATTATTTCGCTTACCAACAACTGCAGA-3', 5'-terminal modified amino group (5NH2C6)) was dissolved in phosphate buffer (10 mM) at pH 8.5 (the concentration of the amino-modified low-density lipoprotein aptamer after dissolution was 26.1). The mixture (nmol / 100mL) was mixed with activated SiO2 / PP composite microspheres and reacted with shaking at room temperature for 12 hours in the dark. After the reaction, the microspheres were centrifuged and washed with buffer to remove unbound aptamers, yielding urchin-shaped SiO2 / PDVB / PDA / Apt composite microspheres (SiO2 / PP / Apt).

[0035] Scanning electron microscope (SEM) and transmission electron microscope (TEM) images of SiO2 / P, SiO2 / PP, and SiO2 / PP / Apt prepared in Example 1 are shown below. Figure 1 As shown, A is the SEM image of SiO2 / P, B is the SEM image of SiO2 / PP, C is the SEM image of SiO2 / PP / Apt, D is the TEM image of SiO2 / P, E is the TEM image of SiO2 / PP, and F is the TEM image of SiO2 / PP / Apt. Figure 1 It can be seen that the surface of the SiO2 / P composite microspheres is uniformly covered with nanofibers, exhibiting a sea urchin-like structure. The morphology of the SiO2 / PP composite microspheres modified with polydopamine and the SiO2 / PP / Apt composite microspheres immobilized with aptamers remains unchanged, and the nanofibers are still tightly attached to the surface of the microspheres, providing a structural basis for the subsequent high adsorption capacity separation of low-density lipoproteins.

[0036] The infrared spectra of SiO2 and the SiO2 / P, SiO2 / PP, and SiO2 / PP / Apt prepared in Example 1 are shown below. Figure 2 As shown, by Figure 2 It can be seen that pure SiO2 at 475 cm⁻¹ -1 The region exhibits characteristic bending vibration peaks of Si-O-Si or O-Si-O at ~1100 cm⁻¹. -1 and ~800 cm -1 The vibrations at ~3415 cm⁻¹ belong to the asymmetric and symmetric stretching vibrations of Si-O-Si, respectively. -1 and ~1635 cm -1The values ​​at these locations are attributed to the stretching and bending vibrations of the silanol group, respectively. After PDVB modification, the SiO2 / P ratio is ~1510 cm⁻¹. -1 The characteristic peak of the stretching vibration of the aromatic ring C=C skeleton appears at ~2930 cm⁻¹. -1 and ~2850 cm - A characteristic peak of the methylene CH bond stretching vibration appears at position ¹, along with a Si-O-Si peak (~1100 cm⁻¹). -1 The spectrum broadens due to the superposition effect, confirming that PDVB has been successfully coated onto the silica surface. In the FTIR spectrum of SiO2 / PP, the phenolic hydroxyl CO stretching vibration (~1052 cm⁻¹) is observed. -1 ) and aromatic ring C=C / C=N stretching vibration (1610~1567cm) -1 The absorption peak of the NH / OH stretching vibration was significantly enhanced (~3348 cm⁻¹). -1 The broadening of the absorption band, consistent with the characteristic absorption of polydopamine, indicates successful modification of the dopamine layer. Further coupling with an aptamer resulted in the SiO2 / PP / Apt absorption band at ~3432 cm⁻¹. -1 The OH / NH stretching vibration peak at this location becomes stronger and broader, reaching ~1633 cm⁻¹. -1 The enhanced C=O stretching vibration peak of the amide I band indicates that the aptamer has been successfully covalently bonded to the material surface. The appearance, enhancement, and superposition evolution of the aforementioned infrared characteristic peaks successively confirm the successful progress of each step of surface modification.

[0037] Thermogravimetric analysis curves of SiO2 and SiO2 / P, SiO2 / PP, and SiO2 / PP / Apt prepared in Example 1 are shown below. Figure 3 As shown. By Figure 3 It can be seen that pure SiO2 exhibits good thermal stability within the test temperature range under a nitrogen atmosphere. The mass loss in the temperature range of 30–200 °C is mainly attributed to the removal of surface water molecules. With further increases in temperature, the continued mass loss is primarily attributed to the decomposition of chemically bonded surface-modified molecules. When the temperature rises to 500 °C, the residual weights of SiO2 / P, SiO2 / PP, and SiO2 / PP / Apt all decrease to varying degrees compared to pure SiO2, with SiO2 / PP / Apt showing the largest decrease, reducing its residual weight to 67% of its initial weight. These results indicate that PDVB, PDA, and the aptamer have been successfully and sequentially modified onto the silica surface.

[0038] XPS full spectra and high-resolution C1s, N 1s, and O 1s spectra of SiO2 and SiO2 / P, SiO2 / PP, and SiO2 / PP / Apt prepared in Example 1 are shown below. Figure 4 As shown, in the full spectrum ( Figure 4In A), pure SiO2 is mainly composed of O and Si; after PDVB polymerization, the XPS spectrum of SiO2 / P shows a characteristic peak of C; after PDA modification, a new N 1s peak appears at 399.8 eV in the XPS spectra of SiO2 / PP and SiO2 / PP / Apt, originating from the polydopamine layer on the material surface. Meanwhile, the Si 2s and Si 2p signals are significantly weakened after PDVB, PDA, and aptamer modification. In the high-resolution C 1s spectrum (… Figure 4 In (B), SiO2 / P corresponds to Si-C / CC bonds and CO bonds at 284.8 eV and 286.4 eV, respectively; after PDA modification, the CO bond characteristic peak is enhanced, and a C=O bond peak appears at 287.9 ​​eV; after further modification of the aptamer, the CO characteristic peak is significantly enhanced due to the presence of the aptamer deoxyribose ring (CO). In the N 1s spectrum ( Figure 4 In C), SiO2 / PP has a C=NH structure at 398.4 eV and a -NH- structure at 399.9 eV; after immobilization of the amino-functionalized aptamer, the characteristic peak of the aromatic nitrogen (CN=C) base appears at 399.2 eV in the N 1s spectrum of SiO2 / PP / Apt. In the O 1s spectrum ( Figure 4 In step D), the Si-O bond in pure SiO2 is located at 532.8 eV; after PDVB surface polymerization, a new Si-OC signal peak appears at 532.9 eV in the O1s spectrum; after further modification of PDA, the OC / OH characteristic peak at 533.4 eV, attributed to the phenolic hydroxyl / hydroxyl groups in PDA, appears; after aptamer modification, the CO / C-OH characteristic peak appears and its intensity increases. These results fully confirm the successful modification of surface functional groups at each step in the composite material.

[0039] Example 2 Adsorption experiments were conducted in 40 mM Britton-Robinson (BR) buffer at a low-density lipoprotein (LDL) concentration of 15 μg / mL and an adsorbent dosage ranging from 10 to 90 μg. Adsorption time experiments were performed at adsorption times ranging from 5 to 50 min. During adsorption, the adsorption capacity was monitored using a fluorescence spectrophotometer.

[0040] (1) The effect of adsorbent (SiO2 / PDVB / PDA / Apt composite microspheres) dosage and adsorption time on adsorption efficiency is shown in the figure. Figure 5 As shown, A represents the amount of SiO2 / PDVB / PDA / Apt composite microspheres, and B represents the adsorption time of the SiO2 / PDVB / PDA / Apt composite. Figure 5A showed that the adsorption efficiency of low-density lipoprotein (LDL) reached its maximum when the adsorbent dosage was 60 μg (LDL concentration 15 μg / mL, buffer volume 300 μL, adsorption time 30 min). Further increasing the adsorbent dosage did not improve the LDL adsorption efficiency. Figure 5 B shows that, under the conditions of SiO2 / PP / Apt dosage of 60 μg and LDL concentration of 15 μg / mL, the adsorption efficiency of LDL increases with increasing adsorption time, reaching a maximum of 94.7% at 30 min. Further extending the adsorption time does not contribute to improving the adsorption efficiency.

[0041] (2) Effect of pH value on adsorption efficiency: The effect of pH on the adsorption efficiency of low-density lipoprotein was investigated within the pH range of 3.0 to 9.0. The results are as follows: Figure 6 As shown in Figure A, the adsorption efficiencies of SiO2, SiO2 / PP, and SiO2 / PP / Apt for low-density lipoprotein (LDL) all showed a trend of first increasing and then decreasing with pH changes, reaching their highest values ​​at pH 5.5. This phenomenon is closely related to the isoelectric point (pI≈5.5) of LDL and the surface charge state of the materials. When the pH of the system is equal to the isoelectric point (5.5) of LDL, the overall net charge of LDL approaches zero, and the electrostatic repulsion between LDL molecules is minimal, which is conducive to the tight stacking and adsorption of proteins on the adsorbent surface. At the same time, at this pH value, strong electrostatic attraction can be formed between the locally positively charged regions (basic residues) exposed on the surface of LDL and the negatively charged phosphate backbone of the nucleic acid aptamers on the surface of SiO2 / PP / Apt. The amino and phenolic hydroxyl groups of polydopamine on the surface of SiO2 / PP can also form hydrogen bonds or electrostatic synergistic effects with the locally negatively charged regions of LDL (such as sialic acid residues). When the pH of the adsorption system deviates from 5.5, the adsorption efficiency of the adsorbent for low-density lipoprotein (LDL) decreases significantly. When pH < 5.5, LDL carries a positive charge. Although there is electrostatic attraction with the negatively charged aptamer, the strong positive charge leads to strong electrostatic repulsion between LDL molecules, hindering their tight assembly on the surface of the adsorbent microspheres. Simultaneously, under strong acid conditions, a large number of amino groups on the polydopamine surface are protonated (becoming positively charged), weakening the mutual attraction between SiO2 / PP and the positively charged LDL, and potentially causing localized shrinkage of the aptamer conformation. When pH > 5.5, LDL carries a negative charge, and both the aptamer backbone and the phenolic hydroxyl groups of the polydopamine are deprotonated and negatively charged. Strong electrostatic repulsion occurs between the material and LDL, leading to a sharp decrease in LDL adsorption efficiency.

[0042] (3) Effect of ionic strength on adsorption efficiency: Using SiO2 / PP / Apt as the adsorbent, the effect of ionic strength (NaCl concentration: 0–2.0 mol / L) on the adsorption efficiency of low-density lipoprotein was further investigated at pH 5.5. The results are as follows: Figure 6 As shown in Figure B, the adsorption efficiency of low-density lipoprotein (LDL) decreases significantly with increasing NaCl concentration. When the NaCl concentration reaches 1.0 mol / L, the LDL adsorption efficiency decreases by more than 70%. This is because the charge shielding effect generated by the high concentration of external electrolyte compresses the diffuse electric double layer of the adsorbent, greatly reducing the electrostatic attraction between the locally charged regions on the LDL surface and the polydopamine / aptamer. This result strongly demonstrates that electrostatic interactions play a central role in the LDL adsorption process.

[0043] Example 3 Human serum albumin (HSA), α-lactalbumin (α-La), β-lactoglobulin (β-Lg), and high-density lipoprotein (HDL), which has a structure similar to low-density lipoprotein, were selected as interfering proteins. The selective adsorption capacity of SiO2 / PP / Apt for low-density lipoprotein was investigated under the same conditions. The adsorption conditions were: BR buffer at pH 5.5, a protein concentration of 15 μg / mL, an adsorbent dosage (SiO2, SiO2 / PP, and SiO2 / PP / Apt) of 60 μg, and an adsorption time of 30 min. The results are as follows: Figure 7 As shown, pure SiO2 and SiO2 / PP microspheres without aptamers exhibited non-specific adsorption for all five proteins, with adsorption efficiencies ranging from 40% to 65%. After the introduction of aptamers, the adsorption rate of SiO2 / PP / Apt for low-density lipoprotein significantly increased to over 90%, while the adsorption rates for the four interfering proteins were significantly lower than 40%. This superior specificity can be attributed to the following two points: (1) Electrostatic repulsion: Under the adsorption conditions of pH 5.5, HSA (pI 4.7), α-La (pI 4.2), and β-Lg (pI 5.2) all carry negative or weak negative charges, generating strong electrostatic repulsion between them and the phosphate backbone of the aptamer with negative charges on its surface; (2) Conformation-specific recognition: Although HDL and LDL are structurally similar lipoproteins, the low-density lipoprotein aptamer only specifically recognizes the specific spatial conformation of apolipoprotein B-100 on the surface of low-density lipoprotein, while the surface of high-density lipoprotein does not contain this binding site, effectively avoiding cross-interference. The above results fully demonstrate that the composite material has extremely high selectivity for low-density lipoprotein.

[0044] The adsorption capacity of the adsorbent (SiO2 / PP / Apt) for protein was determined in the range of 1–400 μg / mL, and the results are as follows: Figure 8As shown, the equilibrium adsorption capacity of SiO2 / PP / Apt for low-density lipoprotein increases rapidly with increasing protein concentration, tending to saturate in the high concentration range, with a maximum experimental adsorption capacity of approximately 2700 μg / mg. In contrast, the adsorption capacities of SiO2 / PP / Apt for the other four interfering proteins (HDL, HSA, α-La, and β-Lg) are all below 800 μg / mg, further confirming the high affinity of the composite material for low-density lipoprotein.

[0045] The adsorption capacities of SiO2 / PP / Apt and SiO2 / PP for different concentrations of low-density lipoprotein (LDL) are as follows: Figure 9 As shown in Figure A, the adsorption effect of SiO2 / PP / Apt on low-density lipoprotein is significantly better than that of SiO2 / PP. The adsorption isotherm data of SiO2 / PP / Apt and SiO2 / PP were linearly fitted using the Langmuir isotherm model. The Langmuir linear expression is: 1 / Q e = K d / (Q max × C e ) + 1 / Q max Among them, Q e To achieve the equilibrium adsorption capacity (μg / mg), C e To achieve the equilibrium concentration (μg / mL), Q max For the maximum adsorption capacity (μg / mg), K d is the dissociation constant (μg / mL).

[0046] The adsorption isotherms of SiO2 / PP / Apt and SiO2 / PP are shown below. Figure 9 As shown in Figure B, the fitting results indicate that the linear correlation coefficients (R²) for SiO₂ / PP / Apt and SiO₂ / PP are as high as 0.9915 and 0.9962, respectively, suggesting that the adsorption behavior of low-density lipoprotein on the microsphere surface conforms to the monolayer adsorption model. Based on the intercept calculation of the linear regression equation, the intercept for SiO₂ / PP / Apt is 0.00036, with a maximum adsorption capacity of 2777 μg / mg; the intercept for SiO₂ / PP is 0.0087, with a maximum adsorption capacity of approximately 1149 μg / mg. The comparison shows that the theoretical maximum adsorption capacity of the material modified with aptamers increased by 2.42 times. This result indicates that the aptamer not only endows the material with specific recognition capabilities but also significantly enhances the adsorption capacity of the material for low-density lipoprotein through its unique spatial binding sites. The high degree of agreement with the Langmuir model further suggests that the adsorption process is mainly driven by chemical interactions (i.e., the specific affinity between the aptamer and the target analyte).

[0047] The SiO2 / PP / Apt microspheres prepared in this invention exhibit a significantly higher maximum adsorption capacity than similar materials. This superior adsorption performance is mainly attributed to the following two aspects: (1) Macroscopically unique structure: The "sea urchin"-shaped nanofiber network formed by PDVB polymerization greatly expands the attachment space for low-density lipoproteins; (2) Microscopic specificity and high affinity: The polydopamine interlayer not only improves the water dispersibility of the material but also acts as a bridge to stably connect the low-density lipoprotein aptamers. The aptamers form a high-affinity specific binding with the low-density lipoprotein target, thereby enhancing the monolayer adsorption capacity. Combining its excellent specificity, rapid adsorption equilibrium, and mild elution performance, the SiO2 / PP / Apt microspheres demonstrate significant competitiveness in the efficient separation of low-density lipoproteins.

[0048] Example 4 The complementary DNA strand of the low-density lipoprotein aptamer was used as the eluent to elute (elution conditions were the same as adsorption conditions) the SiO2 / PDVB / PDA / Apt composite microspheres adsorbed with low-density lipoprotein in the above examples. The elution efficiency of low-density lipoprotein was investigated at different elution times. The results are as follows: Figure 10 As shown, the elution efficiency increased significantly with time, reaching a peak (85%) at elution time of 40 min. Further extension of the elution time did not reveal a significant change in efficiency. This indicates that the base-pairing competition between the aptamer and its complementary strand is highly effective, rapidly disrupting the specific binding between the aptamer and low-density lipoprotein, thereby releasing the target protein from the microsphere surface.

[0049] During elution, the structural integrity of low-density lipoprotein (LDL) is crucial for its subsequent analysis or reuse. The total cholesterol content in the samples before and after elution was determined using the classic sulfur-phosphorus-iron colorimetric method to assess the retention of the core lipid components of LDL during adsorption / elution. The results showed that when the initial LDL concentration was 10, 15, and 20 μg / mL, the cholesterol recovery rates from LDL after adsorption and elution reached 82.3%, 84.5%, and 83.8%, respectively. This indicates that although the entire adsorption / desorption cycle was highly efficient, it did not compromise the structural integrity of the LDL lipoprotein core (no significant cholesterol loss), demonstrating that the adsorption-separation process was mild and effectively maintained the native conformation and integrity of LDL.

[0050] Example 5 Adsorption and recovery experiments were conducted using a goat serum model simulating hyperlipidemia. A low-density lipoprotein (LDL) standard solution was added to commercially available goat serum to achieve a final LDL concentration of 2.0 mg / mL, corresponding to clinically relevant hyperlipidemia levels. Protein components at each separation stage were characterized using SDS-PAGE, and the electrophoresis results are shown below. Figure 11As shown, lane 1 is the protein molecular weight standard (marker); lane 2 is a goat serum sample with added exogenous low-density lipoprotein standard. A clear low-density lipoprotein characteristic protein band (i.e., apolipoprotein B-100) can be observed at approximately 110 kDa on the gel (corresponding to the high molecular weight region indicated by the red arrow). At the same time, bands of various naturally occurring mixed proteins in the serum are clearly visible, presenting a typical complex matrix background; lane 3 is the supernatant after SiO2 / PP / Apt adsorption treatment. It can be observed that the previously significant low-density lipoprotein characteristic band has been effectively removed, while the remaining serum background protein bands remain intact, fully demonstrating that the microspheres can highly specifically recognize and capture the target low-density lipoprotein in complex protein mixtures without producing significant non-specific adsorption; lane 4 is the protein solution recovered after competitive elution with aptamer complementary strands. Only a single clear band is shown in the figure, and its migration position is completely consistent with the low-density lipoprotein standard in lane 5, indicating that the elution and recovery process achieved extremely high purity.

[0051] The above results provide a clear and compelling demonstration that the "sea urchin"-shaped composite material possesses dual advantages in complex biological liquid matrices: it can serve as a highly efficient adsorbent for targeted removal of low-density lipoprotein (LDL) from serum, and as a gentle release agent for the recovery of high-purity LDL. Combined with the cholesterol recovery data mentioned above, this separation and recovery process did not damage the native lipoprotein core structure of LDL. The comprehensive performance of "specific recognition-efficient capture-gentle elution-structural preservation" provides a highly promising material platform for early clinical screening, separation, purification, and biochemical metabolic research of LDL-related cardiovascular diseases.

[0052] The above embodiments of the present invention are merely examples for clearly illustrating the present invention and are not intended to limit the implementation of the present invention. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is impossible to exhaustively list all possible implementations here. All obvious variations or modifications derived from the technical solutions of the present invention are still within the protection scope of the present invention.

Claims

1. A method for preparing urchin-shaped SiO2 / PDVB / PDA / Apt composite microspheres, characterized in that, Includes the following steps: (1) Preparation of SiO2 / PDVB composite microspheres: Silica microspheres were dispersed in an organic solvent containing surfactants, and a catalyst and divinylbenzene were added to carry out cationic polymerization to obtain SiO2 / PDVB composite microspheres; (2) Preparation of SiO2 / PDVB / PDA composite microspheres: The SiO2 / PDVB composite microspheres prepared in step (1) are dispersed in a buffer solution containing dopamine and subjected to an oxidative self-polymerization reaction under weakly alkaline conditions to coat the surface of the SiO2 / PDVB composite microspheres with a polydopamine coating to obtain SiO2 / PDVB / PDA composite microspheres. (3) Preparation of SiO2 / PDVB / PDA / Apt composite microspheres: The SiO2 / PDVB / PDA composite microspheres prepared in step (2) are dispersed in a buffer solution containing amino-modified low-density lipoprotein aptamers and immobilized to obtain SiO2 / PDVB / PDA / Apt composite microspheres.

2. The method for preparing urchin-shaped SiO2 / PDVB / PDA / Apt composite microspheres according to claim 1, characterized in that, The nucleic acid sequence of the amino-modified low-density lipoprotein aptamer described in step (3) is shown in SEQ ID NO.1, with an amino group modified at its 5' end.

3. The method for preparing urchin-shaped SiO2 / PDVB / PDA / Apt composite microspheres according to claim 1, characterized in that, In step (1), the particle size of the silica microspheres is 1~3μm; the catalyst is boron trifluoride diethyl ether; the surfactant is Span 80; and the organic solvent is n-heptane.

4. The method for preparing urchin-shaped SiO2 / PDVB / PDA / Apt composite microspheres according to claim 1, characterized in that, In step (1), the mass ratio of silica microspheres to divinylbenzene is 1:3~8; the catalyst is boron trifluoride diethyl ether; the volume ratio of the catalyst to divinylbenzene is 1:5~15; the amount of surfactant added is 1 / 3~2 / 3 of the mass of silica; and the concentration of silica in the organic solvent is 3~6 mg / mL.

5. The method for preparing urchin-shaped SiO2 / PDVB / PDA / Apt composite microspheres according to claim 1, characterized in that, In step (1), the cationic polymerization reaction is carried out under ultrasonic treatment at room temperature for 10-30 minutes, and anhydrous ethanol is added to terminate the reaction after the reaction is completed.

6. The method for preparing urchin-shaped SiO2 / PDVB / PDA / Apt composite microspheres according to claim 1, characterized in that, In step (2), the concentration of dopamine in the buffer solution is 0.3~1.0 mg / mL; the conditions for the oxidative self-polymerization reaction are: reaction for 20~60 min under weakly alkaline conditions of Tris-HCl buffer at pH 8.0~9.

0.

7. The method for preparing urchin-shaped SiO2 / PDVB / PDA / Apt composite microspheres according to claim 1, characterized in that, In step (3), the concentration of the amino-modified low-density lipoprotein aptamer in the buffer solution is 0.5~5 μmol / L; the buffer solution is a phosphate buffer or Tris-HCl buffer with pH 7.5~9.0; the immobilization reaction conditions are: room temperature, protected from light, and shaking reaction for 6~24h.

8. A sea urchin-shaped SiO2 / PDVB / PDA / Apt composite microsphere prepared by the preparation method according to any one of claims 1 to 7.

9. The application of the sea urchin-shaped SiO2 / PDVB / PDA / Apt composite microspheres prepared by the preparation method according to any one of claims 1 to 8, or the sea urchin-shaped SiO2 / PDVB / PDA / Apt composite microspheres according to claim 9, in the separation or purification of low-density lipoproteins.

10. The application according to claim 9, characterized in that, The purification process involved using the complementary DNA strand of the low-density lipoprotein aptamer as the eluent, with the elution conditions being the same as the adsorption conditions, to obtain high-purity low-density lipoprotein.